ChemInform Abstract: Lithium and Sodium Battery Cathode Materials: Computational Insights into Voltage, Diffusion and Nanostructural Properties. Issue 14 (8th April 2014) - Islam, M. Saiful; Fisher, Craig A. J.
Abstract Review: DFT and atomistic potential‐based methods; 187 refs.